Negative and positive allosteric modulators of the α7 nicotinic acetylcholine receptor regulates the ability of adolescent binge alcohol exposure to enhance adult alcohol consumption - Rodd, Zachary A.; Swartzwelder, H. Scott; Waeiss, R. Aaron; Soloviov, Serhii O.; Lahiri, Debomoy K.; Engleman, Eric A.; Truitt, William A.; Bell, Richard L.; Hauser, Sheketha R. (Frontiers in Behavioral Neuroscience, 2023)
Rationale and Objectives: Ethanol acts directly on the α7 Nicotinic acetylcholine receptor (α7). Adolescent-binge alcohol exposure (ABAE) produces deleterious consequences during adulthood, and data indicate that the α7 receptor regulates these damaging events. Administration of an α7 Negative Allosteric Modulator (NAM) or the cholinesterase inhibitor galantamine can prophylactically prevent adult consequences of ABAE. The goals of the experiments were to determine the effects of co-administration of ethanol and a α7 agonist in the mesolimbic dopamine system and to determine if administration of an α7 NAM or positive allosteric modulator (PAM) modulates the enhancement of adult alcohol drinking produced by ABAE. Methods: In adult rats, ethanol and the α7 agonist AR-R17779 (AR) were microinjected into the posterior VTA, and dopamine levels were measured in the nucleus accumbens shell (AcbSh). In adolescence, rats were treated with the α7 NAM SB-277011-A (SB) or SNU (PAM) 2 hours before administration of EtOH (ABAE). Ethanol consumption (acquisition, maintenance, and relapse) during adulthood was characterized. Results: Ethanol and AR co-administered into the posterior VTA stimulated dopamine release in the AcbSh in a synergistic manner. The increase in alcohol consumption during the acquisition and relapse drinking during adulthood following ABAE was prevented by administration of SB, or enhanced by administration of PNU, prior to EtOH exposure during adolescence. Discussion: Ethanol acts on the α7 receptor, and the α7 receptor regulates the critical effects of ethanol in the brain. The data replicate the findings that cholinergic agents (α7 NAMs) can act prophylactically to reduce the alterations in adult alcohol consumption following ABAE.